ANALISIS TINGKAT PELAYANAN ANGKUTAN KOTA PT TRANEX GPM RUTE BUKITTINGGI – PADANG - Desy Lestary; Ishak Ishak; Elfania Bastian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Bukittinggi is one of the cities in West Sumatra and has the second largest economy in West Sumatra, Indonesia. Considering the growth and development of the city of Padang, most people use public transportation for trade, work and tourism. The population in this study were users of public transportation between cities on the Bukittinggi - Padang route. City transportation PT Tranex Graha Perkasa Mandiri has 8 fleets with executive class buses equipped with air conditioning, the number of passenger seats is 16 people with a sample of 97 respondents. The purpose of this study was to determine the performance of public transportation PT Tranex Graha Perkasa Mandiri and determine the level of service. Sampling technique is done by sampling technique. Data was collected by means of a questionnaire. 80% of the respondents surveyed the security conditions in the vehicle are safe or there are no disturbances, both criminal and passenger safety, while 20% of respondents stated that it was not safe. 55% of inter-city public transport vehicle passengers on the Bukittinggi - Padang route who were interviewed stated that the vehicle they were traveling in was moderate, while 30% said it was good and 15% said it was bad. Based on the results of the analysis, it is concluded that the waiting time for PT Tranex Graha Perkasa Mandiri is 60 minutes, which according to service standards is less and the waiting time is 30 minutes less in service standards. Keywords : City Transport, Bukittinggi, service, transportation